Analisis Efektivitas Perangkat 24/7 Berbasis Internet of Things (IoT) Pada Lift Kone Menggunakan Metode Overall Equipment Effectivenes (OEE) Dan Failure Mode And Effects Analysis (FMEA) - Harijaya, Soundy Satriani; Prabowo, Herry Agung (Universitas Mercu Buana, 2020)
In production activities, the value of productivity is quite important to pay attention to. If the productivity value of production activity is low, it can reduce the value of the production, such as not achieving the predetermined target. Therefore, it is quite important to know the value of productivity which can be seen from the value of its effectiveness. One way to determine the value of effectiveness is by using the Overall Equipment Effectiveness (OEE) method. PT. KONE Indo Elevator (KIE), has a new product called 24/7 Connected Services, where the product is targeted to reduce the existing Call Out Rate (COR). In the period of March 2020, the existing COR value is 2.92. Because the product is 24/7 Connected Services, the effectiveness value of the product or device is not yet known, which can be determined using the OEE method, along with the Failure Mode and Effect Analysis (FMEA) method to analyze what types of potential biggest failures are in the product. the. After installing the device from April 2020 to June 2020, the effectiveness value of the device can be analyzed. After analyzing, it was found that the OEE 24/7 Connected Services value was 88.36% with the sample data for 12 weeks. The biggest loss factor of this product is in the reduction speed loss with a value of 10.841% of the total loss. The greatest potential for failure is in the signal problem of the problematic device, with an RPN value of 21, where improvements can be made to add an extender antenna and add a signal amplifier. From the OEE value found, it has exceeded the existing OEE standard value, which is 85%, where 24/7 Connected Services products are 3.36% higher than the existing standard value.